Monitoring of winter rye diseases in Kirov region and possible trends of breeding for immunity - L. M. Shchekleina (Аграрная наука Евро-Северо-Востока, 2020)
The analysis of the phytosanitary situation in production, selection and seed crops of winter rye in Kirov region for the period from 1999 to 2018 was carried out in order to adjust the tasks of breeding for resistance to the most harmful diseases. The affection of the sowings (spread of the disease), the development of the disease and the area of the affected crops relative to the number of the examined ones were evaluated. The trend in the development of the diseases was established on the basis of a regression analysis of long-term data of the branch of the FSBI Rosselkhozcentr in Kirov region. The annual (100 %) manifestation of snow mold and ergot has been established. Next according to the frequency of manifestation there are root rots and brown rust – 95 %, powdery mildew – 75 %, sclerotinia – 70 %, Fusarium head blight – 70 %, and stem rust – 50 %. A relatively low frequency of manifestation has been observed with septoriose and rhynchosporium – 35 and 30 %. However, taking into account the development of winter rye diseases which exceed the economic threshold of harmfulness (ETH), the studied pathocomplexes have different levels of danger. Thus, the development of brown rust above ETH was diagnosed 13 times within 19 years. The most severe disease development (20.0-52.0 %) was in 2001, 2005, 2009, and 2010; weak - in 2007 (0.8 %), 2017 (1.4 %), 2015 (2.4 %), and 2011 (5 %). The manifestation of powdery mildew above ETH was observed 6 times within 15 years, disease development was at the level of 13.0-53.0 %. The development of septoriose above ETH was diagnosed 6 times within 7 years with the development of disease from 13.5 to 63.0 %. Development of stem rust above ETH was diagnosed 5 times within 10 years with the status of the sign of 15.0-20.0 %. The cyclicity of spread of the most harmful diseases and trends of their change in agrocenoses of winter rye are shown. Thus, the most epitphytotically dangerous diseases include snow mold, brown rust, stem rust, powdery mildew and septoriose. Constant control is also required in relation to ergot and Fusarium head blight. These diseases should be an object for breeding-and-immunological studies.